N‐Heterocyclic Carbene Non‐Innocence in the Catalytic Hydrophosphination of Alkynes. Issue 7 (6th March 2019) - Blackaby, William J. M.; Neale, Samuel E.; Isaac, Connie J.; Sabater, Sara; Macgregor, Stuart A.; Whittlesey, Michael K.
Abstract: Studies on alkyne hydrophosphination employing nickel‐NHC catalysts (NHC=N‐heterocyclic carbene) revealed that the free N‐alkyl substituted NHCs themselves were catalytically active. DFT calculations showed the mechanism involves the NHC acting as a Brønsted base to form an imidazolium phosphide species which then undergoes rate‐limiting nucleophilic attack at the terminal alkyne carbon. This mechanism explains the preference seen experimentally for reactions with aryl substituted phosphines and alkynes, while the rearrangements of the alkenyl anion formed upon P−C bond formation account for the observation of both Z ‐ and E ‐regioisomers of the products. Abstract : Free as an NHC : Free N‐alkyl substituted N‐heterocycle carbenes (NHCs) promote the catalytic hydrophosphination of aryl‐substituted alkynes through a mechanism involving nucleophilic attack of an imidazolium phosphide species at the terminal alkyne carbon. These results highlight the potential non‐innocence of NHCs in their use as ligands in metal catalyzed transformations.